A real-world pharmacovigilance analysis of omadacycline in FDA adverse event reporting system (FAERS) database - Shi, Xueping; Wang, Chen; Liu, Xiang; Zou, Li; Guo, Pei (Frontiers in Pharmacology, 2025)
ObjectiveOmadacycline is a newly launched drug of tetracycline. Therefore, it is necessary to comprehensive evaluate reports on the safety of omadacycline in large, real-world populations. This study aimed to mine the adverse event (AE) signals related to omadacycline through the Food and Drug Administration Adverse Event Reporting System (FAERS) database.MethodsData from the FAERS database from 1 January 2004 and 31 March 2024 were queried through OpenVigil 2.1. After the completion of data mapping, we collated and summarized key demographic and clinical characteristics of the reported cases. During the analysis, both Reporting odds ratio (ROR) and Bayesian confidence propagation neural network (BCPNN) were employed for the detection of AE signals.ResultsWe extracted a total of 452 suspected AE cases with omadacycline from the FAERS database. Among them, 69 positive signals were obtained using the ROR and BCPNN. The highest frequency reported systemic organ class (SOC) was gastrointestinal disorders. Common clinical AEs of omadacycline were detected in the FAERS database, such as nausea, vomiting, tongue discolouration, hepatic enzyme increased, and hypersensitivity. In addition, we identified potential unexpected serious AEs through disproportionality analysis, including eosinophilia, pancytopenia, internal haemorrhage, restless legs syndrome, hypoacusis, and tinnitus.ConclusionIn light of the growing use of omadacycline in clinical practice, routinely reviewing data from the FAERS database for signals of AE can help to ensure patient medication safety and enhance overall medical quality.